Professional training in industrial maintenance: A social interactionist approach - Freitas, Carlos Alberto de [UNESP]; Dias, Rubens Alves [UNESP] (SAGE Publications, 2024)
The present article discusses whether higher engineering and technology courses in Brazil prepare students for professional practice in the maintenance segment, froman educational theoretical framework point of view. To achieve this, the theme significance was researched in Scopus and ScienceDirect bases. The work proposal is based on the concepts of teaching and learning by Vygotsky, confronting the methods used by professors’ engineers, which multiply what they learned in higher education courses. In the planned research, we intend to understand the paradigms and skills of the maintainer considering the action research methods, through the ILS tool—Index of Learning Styles by Felder and Solomon. To analyze the students’ learning profile regarding their preferences for receiving information, we discuss the scenarios generated, expecting to design a teaching and learning process centered on students, an assumption based on Vygotsky's cognitive theory, in which an individual's learning process is related to their interaction in the social environment that they are. As a result, the proposed teaching practices made it possible to increase personal interest in learning, and we observed that there was less difference between the students’ learning styles and also noticed the same profile in the four dimensions, both morning and evening scenarios. Students consider themselves active, sensory, visual, and global.
Keywords: education; ILS instrument; social interactionism; Teaching of industrial maintenance